Perceptions of psychiatric-trained nurses on integrating mental health into primary health care in Africa - Busisiwe M. Febana; Mutshidzi Mulondo (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: This review mapped the perceptions of nurses on the integration of mental health services into primary health care (PHC) in low- and middle-income countries (LMICs).